2003
DOI: 10.1046/j.1471-4159.2003.01709.x
|View full text |Cite
|
Sign up to set email alerts
|

Isofurans, but not F2‐isoprostanes, are increased in the substantia nigra of patients with Parkinson's disease and with dementia with Lewy body disease

Abstract: F 2 -isoprostanes (F 2 -IsoPs) are well-established sensitive and specific markers of oxidative stress in vivo. Isofurans (IsoFs) are also products of lipid peroxidation, but in contrast to F 2 -IsoPs, their formation is favored when oxygen tension is increased in vitro or in vivo. Mitochondrial dysfunction in Parkinson's disease (PD) may not only lead to oxidative damage to brain tissue but also potentially result in increased intracellular oxygen tension, thereby influencing relative concentrations of F 2 -I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
1
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(60 citation statements)
references
References 34 publications
(45 reference statements)
0
58
1
1
Order By: Relevance
“…Demonstration of neuroprotection by oral administration of a metal-based catalytic antioxidant is consistent with a large body of literature that suggests oxidative stress as a major therapeutic target for PD. Direct oxidative damage to proteins, lipids, and DNA has been detected in the substantia nigra from human and experimental PD (Dexter et al, , 1994aAlam et al, 1997a,b;Good et al, 1998;Giasson et al, 2000;Przedborski et al, 2001b;Fessel et al, 2003). Indirect evidence for oxidative stress in PD comes from studies showing decreased glutathione, increased iron levels and antioxidant imbalance (Perry et al, 1982;Dexter et al, 1987;Sian et al, 1994;Ara et al, 1998;Jha et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Demonstration of neuroprotection by oral administration of a metal-based catalytic antioxidant is consistent with a large body of literature that suggests oxidative stress as a major therapeutic target for PD. Direct oxidative damage to proteins, lipids, and DNA has been detected in the substantia nigra from human and experimental PD (Dexter et al, , 1994aAlam et al, 1997a,b;Good et al, 1998;Giasson et al, 2000;Przedborski et al, 2001b;Fessel et al, 2003). Indirect evidence for oxidative stress in PD comes from studies showing decreased glutathione, increased iron levels and antioxidant imbalance (Perry et al, 1982;Dexter et al, 1987;Sian et al, 1994;Ara et al, 1998;Jha et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Lipid peroxidation is a well-known mechanism of cellular injury initiated by ROS (Sayre et al, 2001) and numerous studies have demonstrated its role in the pathogenesis of PD (Dexter et al, , 1994aFessel et al, 2003). The hydroaldehydes, MDA and particularly 4-HNE, are the most cytotoxic aldehydes produced in the process of lipid peroxidation (Esterbauer et al, 1991;Beal, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…They are even more abundant than iPs in tissues as diverse as kidney and hippocampus in the rat and may offer an adjunctive approach to the assessment of oxidant stress in vivo (6,7). They are formed preferentially under conditions of elevated oxygen tension (6).…”
Section: Isoprostanes (Ips)mentioning
confidence: 99%
“…Indeed, IsoF levels are significantly higher in substantia nigra in brains from patients with Parkinsons disease compared to age-matched controls. [177] This finding led to the hypothesis that analysis of both F 2 -IsoPs and IsoFs might provide a more complete and reliable index of oxidative stress. Such a determination is easy to achieve since F 2 -IsoPs and IsoFs can be purified on the same TLC plate and simultaneously quantified in a single GC/MS assay by including an additional ion channel for IsoFs, which is 16 Da higher than that for F 2 -IsoPs.…”
Section: Methodsmentioning
confidence: 99%